Morphological features of naevoid melanoma: results of a multicentre study of the International Dermoscopy Society. (1st April 2015) - Longo, C.; Piana, S.; Marghoob, A.; Cavicchini, S.; Rubegni, P.; Cota, C.; Ferrara, G.; Cesinaro, A.M.; Baade, A.; Bencini, P.L.; Mantoux, F.; Mijuskovic, Z.P.; et al.
Summary: Background: Naevoid melanoma (NeM), a rare variant of melanoma, can be difficult to detect as its clinical and histopathological morphology can simulate a naevus. Objectives: To describe the clinical and dermoscopic features associated with NeM. Methods: Lesions with a histopathological diagnosis of NeM were collected via an e‐mail request sent to all members of the International Dermoscopy Society. All lesions were histopathologically reviewed and only lesions fulfilling a set of predefined histopathological criteria were included in the study and analysed for their clinical and dermoscopic features. Results: Twenty‐seven of 58 cases (47%) fulfilled the predefined histopathological criteria for NeM and were included in the study. Clinically, 16 of the 27 NeMs presented as a nodular lesion (59%), eight (30%) as plaque type and three (11%) as papular. Analysis of the global dermoscopic pattern identified three types of NeM. The first were naevus‐like tumours ( n = 13, 48%), typified by a papillomatous surface resembling a dermal naevus. In these lesions local dermoscopic features included irregular dots/globules (46%), multiple milia‐like cysts (38%) and atypical vascular structures (46%). The second type were amelanotic tumours ( n = 8, 30%), typified by an atypical vascular pattern (75%). The third type consisted of tumours displaying a multicomponent pattern ( n = 4, 15%), characterized by classical local melanoma‐specific criteria. Two lesions (7%) were classified as mixed‐pattern tumours as they did not manifest any of the aforementioned patterns. Conclusions: While NeMs may be clinically difficult to differentiate from naevi, any papillomatous lesion displaying dermoscopically atypical vessels and/or irregular dots/globules should prompt consideration for the possible diagnosis of NeM.